A Structural Model to Adolescent Narcissism Based on Basic Psychological Needs: Mediating Role of Alexithymia - Zahra Yaghtin; Azarmidokht Rezaei; Majid Barzegar; Hossein Bagholi (Iranian Evolutionary Educational Psychology Journal)
Objective: Problems related to narcissism can damage a large part of adolescent relationships. At the same time, looking for the prognosis of narcissism can help reduce the risk of developing the disorder. Therefore, the present study aimed to construct a structural model of adolescent narcissism based on basic psychological needs with the mediating role of alexithymia. Methods: The research method was descriptive-correlational using structural equation modeling. The statistical population included all high school students of Shiraz in 2021. Participants were 512 students who were selected by multi-stage cluster random sampling method.  Narcissistic personality scale, alexithymia questionnaire and basic psychological needs scale were used to collect data. Results: The results indicated that basic psychological needs in a negative and significant way and alexithymia in a positive and significant way predicts narcissism. Also, basic psychological needs positively and significantly predict alexithymia. Finally, basic psychological needs through alexithymia can predict narcissism (p <0.01). Conclusions: Based on the findings, it can be concluded that narcissism in adolescents is a phenomenon that is directly and indirectly affected by basic psychological needs. The findings have useful implications for counseling with teenagers.